An approach to an academic content management site integrated with the social network (Research, Society and Development, 2019)
Over the years, the digital social media are present in the people daily lives, such as possibilities for socialization, marketing, dialogue, among others. However, social networks are increasingly present in the academic environment, and in an informal way, it is common to come across the studies groups in online networks, which students of a series, grade or a course, share knowledge and discussions about content, difficulties and experiences. Such groups and aspects may favor and contribute to the academic journey of these students, which may assist in research work or make doubts understandable of a certain content. Thus, in order to use social networks as an instrument in the teaching and learning process, this work aims to propose an approach to an academic content management site integrated with the Facebook social network. This site can provide an environment in which students can get information about jobs, grades and materials, and enable integration among users. The methodology used was qualitative research and the data collection instrument was the questionnaire for data collection. As final considerations, it is expected that the results of this work will be of great importance for the academic environment, allowing a better understanding of the interaction between students and teachers in these cooperation networks, being that Facebook was suitable for educational environments, since it is widely used by students.